INTELLIGENT DIAGNOSTIC SYSTEM OF THE MOBILE DRILLING RIG HOISTING EQUIPMENTS - Buchynskyi, Andrii; Dorohobid, Vadym (Academic journal Industrial Machine Building Civil Engineering, 2022)
The hoist system and braking mechanism of the drilling drawwork of mobile drilling rigs have a significant safety impact on the technological process and its efficiency, and the economic component of their maintenance is significant during the life cycle of the rig. Recommendations have been developed for the formation of a list of controlled parameters for diagnostics of the traveling system (drilling line, hook block, crown block) and brakes of the drawwork. The functioning of such a diagnostic system makes it possible to describe the operational life cycle of the equipment, predict the condition of the equipment, develop mathematical models and maintenance strategies, evaluate their effectiveness and implement continuous improvement and adaptation of technical influences and use of the equipment taking into account its actual condition